Psychosocial Impact of the COVID-19 Pandemic on Smoking Behavior Among University Students in Indonesia - Aldillah Esa Fitri; Rika Hardiyanti Hanifa; Mega Astri; Misbakhul Munir; M. Idham Cholid; Hafid Algristian; Anna Purnamasari Sugijanti (Yayasan Sinergi Kawula Muda, 2026)
The COVID-19 pandemic has profoundly affected mental health and health-related behaviors, including tobacco use. University students represent a vulnerable group due to academic disruptions, social isolation, and lifestyle changes. This cross-sectional study examined the psychosocial impact of the COVID-19 pandemic on smoking behavior among Indonesian university students. An online survey of 62 respondents assessed demographics, smoking status, changes in smoking patterns, and psychosocial factors such as anxiety, stress, mood, and sleep problems. Among participants, 29% were smokers, mostly male (94%) and aged 20–23 years (61%). Conventional tobacco use predominated (83%), while e-cigarettes accounted for 17%. During the pandemic, 61% reported no change in smoking frequency, 33% a moderate increase, and 6% a heavy increase. Interestingly, students with unchanged smoking habits reported higher psychosocial distress, while those who increased smoking reported fewer complaints, suggesting diverse coping strategies. These findings highlight the complex relationship between stress and tobacco use among Indonesian students and underscore the need for integrated mental health and smoking prevention programs in universities.